COHESIVE MARKERS IN SOCIAL MEDIA DISCOURSE: CASE IN INDONESIAN FACEBOOK CONVERSATIONS - M Zainal Muttaqien; Amir Ma’ruf; Tofan Dwi Hardjanto (Linguistik Indonesia, 2019)
AbstractThe emergence of social media as a new channel of communication has produced a new form discourse which has different characteristics compared to the formerly established conventional discourses. These differences do not only lie in how the messages are delivered but also in their  structural components which contribute to the unity of the text, namely cohesion and coherence. Cohesion, as the marker of coherence, is realized by language units (words, phrases, or clauses) known as cohesive markers which indicate the relationship between parts of discourse either grammatically or lexically. This article aims at describing the composition and distribution of  cohesive markers within the Facebook conversations along with their roles in determining the characteristics of the discourse. The results show that the cohesive system of Facebook conversations are dominated by references, ellipses, repetitions, and conjunctions. The frequent appearances of certain referential cohesivemarkers indicate Facebook conversations as typical of interactive discourse whereas numerous ellipses and particular conjunctionsreflectthe informal mode of communication carried out through the social media.On the other hand, various repetitions show the existence of topical cohesionwithin the conversations.